Engr. Environmental Impact Assessment of the Construction of Airport in Ekiti State - Oyebode, Oluwadare Joshua (International Journal For Research In Advanced Computer Science And Engineering, 2018)
A well-designed airport system is a prime requisite for industrial development, operational safety, efficiency and economic sustainability of a state. The method used is the EIA is the public participation method. In carrying out public participation, a questionnaire needs to be prepared so that the answers of the public can be analyzed and used in making a final conclusion on the project. In my own case, over 90% of my study group agreed that Ekiti state needed an airport, but the same 90% also agreed that the state isn’t ready yet for a project of this scale, considering the negative impacts of the airport construction and the cost of maintaining an airport. All the results of my questionnaire helped me in making my final decision, which is that Ekiti state is not yet ready for the construction of an airport considering the negative impacts of an airport on the environment. I recommend that if the project is considered in the future, the measures recommended to tackle or maintain the negative impacts of an airport construction be put in place in the airport master plan and strict regulations should be put in place to ensure they are adhered to strictly.